2019
DOI: 10.1021/acsanm.9b01206
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Removal of Azo-Dyes in Aqueous Solution by CeB6Nanocrystals

Abstract: Rare earth oxides have been well-developed for the treatment of synthetic dyes in wastewater, but limited information is known regarding the application of other rare earth containing materials in this field. Herein, cerium hexaborides (CeB6) were synthesized via the reaction of CeF3 and NaBH4 in molten LiCl–KCl at 900 °C. Homogeneously dispersed CeB6 nanocrystals exhibit great performances for the removal of azo-dyes such as Congo red (CR). It follows pseudo-second-order kinetics, and a maximum removal capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 75 publications
(89 reference statements)
1
7
0
Order By: Relevance
“…Four oxidation states were identified by deconvolution of the high-resolution Mo 3d XPS spectrum. Mo 0 corresponds to the molybdenum of molybdenum boride, while Mo 3+ , Mo 5+ , and Mo 6+ should result from the surface oxidation of α-MoB 2 (Figure a) that are in line with the results of the molybdenum boride materials reported previously. , Figure b shows the B 1s region, and the intense peak at 188.21 eV corresponds to B in molybdenum boride, which is almost the same as that in other molybdenum borides. , Amorphous B and boron suboxides should be responsible for the 186.61 and 192.36 eV peaks. , …”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Four oxidation states were identified by deconvolution of the high-resolution Mo 3d XPS spectrum. Mo 0 corresponds to the molybdenum of molybdenum boride, while Mo 3+ , Mo 5+ , and Mo 6+ should result from the surface oxidation of α-MoB 2 (Figure a) that are in line with the results of the molybdenum boride materials reported previously. , Figure b shows the B 1s region, and the intense peak at 188.21 eV corresponds to B in molybdenum boride, which is almost the same as that in other molybdenum borides. , Amorphous B and boron suboxides should be responsible for the 186.61 and 192.36 eV peaks. , …”
Section: Resultssupporting
confidence: 86%
“…20,23 Figure 2b shows the B 1s region, and the intense peak at 188.21 eV corresponds to B in molybdenum boride, which is almost the same as that in other molybdenum borides. 23,41 Amorphous B 32 and boron suboxides should be responsible for the 186.61 and 192.36 eV peaks. 41,42 SEM and TEM were employed to explore the morphology and microstructure of the as-prepared α-MoB 2 .…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…[123] Ceramic Templates: Hollow nanoboxes could synthesize by templating against copper oxide nanocubes. [124] Inorganic and complex salts by hard template strategy:…”
Section: Metal-based Templatesmentioning
confidence: 99%
“…It has been reported that molten salt synthesis is a simple and versatile route that favors the phase and size controllable preparation of metal boride nanoparticles. This method has been used to prepare nanoscale electrocatalysts, including oxides and borides. For β-MoB 2 , although it is intrinsically less active than α-MoB 2 as an electrocatalyst for the HER due to the presence of both flat graphene-like and puckered phosphorene-like B layers, it is possible to significantly improve its electrocatalytic performance via nanostructuring, which favors a larger surface area . Herein, single-crystalline phase β-MoB 2 nanosheets were synthesized for the first time via the reaction of MoCl 3 and B powders in molten LiCl-KCl for 4 h at 850 °C.…”
Section: Introductionmentioning
confidence: 99%